2021
DOI: 10.1002/pc.26435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes reinforcement on eigenmodes of multi‐smart core sandwich composite cylindrical shell panels

Abstract: This study investigates the dynamic responses of carbon nanotubes (CNT) reinforced composite sandwich shells with multi magnetorheological elastomer (MRE) core. The CNT reinforced composite skin layers are made by using hand layup technique. An experimental modal test has been carried for with and without CNT reinforced composite cylindrical shells under clamped free condition. The 3D finite element model is verified by comparing the obtained natural frequencies with experimental results. The numerical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The laminated composite cylindrical sandwich shells are modeled and simulated using ABAQUS software. [ 31 ] The material properties considered in Selvaraj et al [ 29 ] : E 1 = 29.49 GPa , E 2 = 6.80 GPa , ν 12 = 0.27, G 12 = 2.71 GPa , G 23 = 2.43 GPa , ρ = 1724 kg/m 3 , G c = 0.6396 MPa, and ρ c = 2384.2 kg/m 3 . The geometry dimensions considered for the simulation are length 0.3 m, width 0.3 m, radius of curvature (R) 0.8 m, core thickness 1 mm and face sheet thickness 1.3 mm.…”
Section: Convergence and Verification Studymentioning
confidence: 99%
“…The laminated composite cylindrical sandwich shells are modeled and simulated using ABAQUS software. [ 31 ] The material properties considered in Selvaraj et al [ 29 ] : E 1 = 29.49 GPa , E 2 = 6.80 GPa , ν 12 = 0.27, G 12 = 2.71 GPa , G 23 = 2.43 GPa , ρ = 1724 kg/m 3 , G c = 0.6396 MPa, and ρ c = 2384.2 kg/m 3 . The geometry dimensions considered for the simulation are length 0.3 m, width 0.3 m, radius of curvature (R) 0.8 m, core thickness 1 mm and face sheet thickness 1.3 mm.…”
Section: Convergence and Verification Studymentioning
confidence: 99%
“…According to Selvaraj et al, 32 multicore sandwich beams vibrational behavior was analyzed numerically and experimentally. Shankar et al 33 used multimagnetorheological elastomer (MRE) cores to examine the dynamic responses of composite sandwich cylindrical shells with carbon nanotubes (CNT) reinforcement. The results showed that the multi‐MRE core sandwich shells have higher natural frequencies than those of single‐MRE‐core sandwich shells, and that inclusion of CNT improves the natural frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization with two different types of reinforcement, whether natural or synthetic, is widely used in the polymer industry. This allows designers to create products with specialized mechanical properties, such as low moisture permeability and strong fiber-matrix bonding [11][12][13][14][15][16][17]. Hybridization has a beneficial effect on storage modulus, loss modulus, and Glass transition temperature in the Jute-Sisal hybrid fiber-reinforced epoxy biocomposite with varying fibre weight ratios [18].…”
Section: Introductionmentioning
confidence: 99%